Quasi‐one‐dimensional gold grating with Si3N4 cap layer as optical coupler for AlGaN/GaN quantum well infrared photodetector. Issue 5 (22nd December 2015) - Wang, Shuai; Wu, Feng; Zhang, Jun; Long, Hanling; Gong, Zheng; Dai, Jiangnan; Chen, Changqing
Abstract: Quasi‐one‐dimensional gold grating with Si3 N4 cap layer has been studied to enhance the optical coupling of AlGaN/GaN quantum well infrared photodetector (QWIP) by finite element method (FEM). The averaged |Ez | 2 across the whole quantum well region reaches 1.49 (V/m) 2 when the electric field intensity (|E0 | 2 ) of normal incidence is 1 (V/m) 2 at 4.6 μm, showing 1.9 times increase compared with that obtained via bare gold grating. The results show that Si3 N4 cap layer plays an indispensable role in inducing the electric field component Ez perpendicular to multi‐quantum wells (MQWs) via not only decreasing the Fresnel reflection but also exciting stronger plasmonic resonance on the upper surface of the quasi‐one‐dimensional gold grating. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)